Evaluation of second-trimester maternal serum betatrophin levels and lipid and carbohydrate metabolism parameters in patients with gestational diabetes mellitus - Bulmus, Funda Gulcu; Melekoglu, Rauf; Gursu, Mehmet Ferit; Bagci, Helin; Kavak, Ebru Celik; Akyol, Alpaslan (Galenos Publ House, 2020)
Objective: We investigated the role of betatrophin in the etiopathogenesis of gestational diabetes mellitus (GDM) and its association with lipid and carbohydrate metabolism in patients with GDM and normoglycemic pregnant women. Materials and Methods: A total of 60 patients [30 pregnant women with GDM (study group) and 30 healthy age-, body mass index-, and gestational age-matched pregnant women (control group)] were included in this study. Serum betatrophin, fasting glucose, insulin, glycated hemoglobin A1c (HbA1c), and C-peptide levels, as well as lipid parameters, were measured. Results: Serum betatrophin, fasting glucose, HbA1c, insulin, and C-peptide levels were significantly higher in the GDM group than in the control group (p<0.001, p=0.009, p=0.013, p<0.001, and p<0.001, respectively). Levels of triglycerides and very-low-density lipoprotein cholesterol were significantly higher in the GDM group (p=0.020 and p=0.020, respectively), but total cholesterol and LDL cholesterol levels were similar in the two groups (p=0.810 and p=0.273, respectively). Betatrophin levels in the GDM group were correlated positively with insulin levels (r=0.336, p=0.009) and the homeostatic model assessment of insulin resistance (HOMA-IR) score (r=0.269, p=0.038), and negatively with the C-peptide levels (r=-0.399, p=0.002); they were not correlated with any other glucose or lipid parameters. Multivariate stepwise linear regression analysis demonstrated that insulin levels (beta=0.134, p=0.013) and the HOMA-IR score (beta=0.112, p=0.017) were associated independently with serum betatrophin levels. Conclusion: These results demonstrate that serum betatrophin levels were significantly higher in pregnant women with GDM than in normoglycemic pregnant women. The levels of betatrophin were correlated significantly with insulin resistance parameters, which is a key feature of GDM pathophysiology.
Gestasyonel diabetes mellituslu hastalarda ikinci trimester maternal serum betatropin düzeyleri ve lipid ve karbonhidrat metabolizması parametrelerinin değerlendirilmesi
Keywords: Betatrophin; gestational diabetes mellitus; insulin resistance